Retorika Politik Dalam Pemilu 2019 dan Cerminan Budaya Kekerasan - Nabila Auliani Ruray (Budapest International Research and Critics University, 2018)
In recent years, the screen of Indonesian society has been filled with controversies about the use of certain words. Social media and news portals boast about Fadli Zon's poem entitled 'There is a Genderuwo in the Palace,' which was later answered by Arsul Sani's poem entitled 'There is a Genderuwo in Senayan.' This incident did not appear suddenly. Previously, local political elites such as Jokowi used the phrase 'Genderuwo politics,' 'sontoloyo politicians,' and Prabowo with a 'Boyolali look' expressed in several different speeches. Given the Indonesian context that entered the 2019 Election, the words and phrases 'masterpieces' were managed to wrinkle many of these brow is nothing but a part of the political attitude of the writer. Submission of written and oral words with the aim of satisfying the arrangement of the political attitude of the whole is indeed a common thing. However, the unusual use of words and phrases in the phenomenon of the Indonesian political year becomes interesting when the formulation of the language comes in the euphemism.